Pengembangan Buku Pengajaran Mikro Berbasis Life Based Learning Untuk Meningkatkan Kapabilitas Mahasiswa Pada Matakuliah Kemampuan Dasar Mengajar - Sulastri, Sulastri; Bahtiar, Moh Danang; Putri, Dhika Maha; Inayati, Ro’ufah (Jurnal Pendidikan Akuntansi (JPAK), 2020)
This study aims to develop a Life Based Learning-based Micro Teaching book, namely the application of basic teaching skills using a scientific approach so that later they are able to increase the capability of Accounting Education students in applying basic teaching skills to real learning in schools in accordance with the demands of curriculum development. education. This research is research and development. The development model used in this research is the IDI (Instructional Development Institute) development model which includes 3 stages, namely define, develop and evaluate. Based on the results of the study, it was shown that the results of developing micro-teaching books based on life-based learning with a scientific approach were declared valid and feasible. used as a learning medium and as a media to support learning in microteaching courses. the textbook was approved to be used as a learning medium in microteaching courses. On average, students find it helpful to understand the scientific approach with the renewal of teaching materials for microteaching courses, this of course can increase their capabilities (as prospective teachers), in facing the challenges of curriculum changes. The development of Life Based Learning-based Micro Teaching books is a must for lecturers, because it can increase student capabilities, especially accounting education study programs which incidentally are teacher candidates in developing basic teaching skills in accordance with the demands of the current development of primary and secondary education curriculum.